2018
DOI: 10.5577/intdentres.2018.vol8.no1.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of knowledge, attitude and practice toward oral health between pediatricians and family doctors

Abstract: Aim: Pediatricians and family doctors are at the first step in the education of parents about oral health, as well as the prevention of oral diseases and the provision of oral health in children. The aim of this study is to evaluate the knowledge, attitudes, and practices of pediatricians and family doctors about oral health in children. Methodology: A questionnaire consisting of 50 items was sent to pediatrician and family doctors via mail. Descriptive analysis and ttests were done to analyze the data. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similar results were observed in a comprehensive European survey, in which 97% of respondents agreed that such examinations were essential [28]. In contrast, the results from Turkey were mixed: 85.7% of family physicians did not examine children's oral cavities, and pediatricians did so only when problems occurred (44.8%) or at the mother's request (31.0%) [29]. Another study from Saudi Arabia indicated that 43.6% of participants reported conducting routine examinations for children, with pediatricians (64.8%) demonstrating significantly better practice compared to family physicians (35.2%) [7].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar results were observed in a comprehensive European survey, in which 97% of respondents agreed that such examinations were essential [28]. In contrast, the results from Turkey were mixed: 85.7% of family physicians did not examine children's oral cavities, and pediatricians did so only when problems occurred (44.8%) or at the mother's request (31.0%) [29]. Another study from Saudi Arabia indicated that 43.6% of participants reported conducting routine examinations for children, with pediatricians (64.8%) demonstrating significantly better practice compared to family physicians (35.2%) [7].…”
Section: Discussionsupporting
confidence: 63%
“…Comparing these results with those of other studies, a study from Saudi Arabia found that 45% of family physicians and slightly more than half of pediatricians (54.8%) had this knowledge [26]. A survey conducted in Turkey, which included family physicians and pediatricians, showed that nearly one-third of family physicians (32%) and a much higher proportion of pediatricians (88%) were aware of this mode of transmission [29]. The research results from Qatar are devastating, with 84% of respondents who participated in the study conducted among general practitioners and pediatricians being unaware of the possibility of bacterial transmission [18].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These results are similar to those reported by Sabbagh et al and Gupta et al [ 14 , 18 ]. Gezgin et al reported that only 44.8% of the study participants examined the oral cavity in the presence of a problem [ 24 ]. As mentioned before, social desirability, in addition to cultural and educational factors, might have resulted in these differences.…”
Section: Discussionmentioning
confidence: 99%